The Utilization Of Audio Visual Media In Increasing Students Listening Skills - Hawema, Solwina (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2023)
The study aimed to address the low listening ability of grade VII students in Arabic Listening Skill at SMP Muhammadiyah 2 Gisting. Educators previously used audio-visual media, but the results were not optimal because the media was only used once. The research used Classroom Action Research (CAR) with the Kurt Lewin model to answer two questions: (1) How is the implementation of the use of audio-visual media in improving listening skills (maharah istima') for grade VII students of SMP Muhammadiyah 2 Giting? (2) Can the use of audio-visual media improve the listening ability of grade VII students at SMP Muhammadiyah 2 Giting? The results of the study showed that the use of audio-visual media can improve the listening ability of grade VII students at SMP Muhammadiyah 2 Gisting.